Signal Processing to Overcome Random Vibration Interference in an Oil Debris Monitor (ODM) Sensor - Chen, Weihong (Université d'Ottawa / University of Ottawa, 2012)
Online Oil Debris Monitors (ODM) provide a direct, effective and reliable approach to machinery condition monitoring. ODM can be used to monitor the condition of complex machines, such as airplane engines, electric generators, wind turbines, or other machines with oil circulation systems. The principle of the sensor is to detect the quantity and the size of metal particles in the flowing oil. The current available ODM sensors suffer from sensitivity to vibrations, as their electromagnetic response is largely affected by interfering vibrations. This thesis presents a novel structure and algorithms to separate and eliminate the vibration interference. In the new structure, a dual channel system is designed as opposed to previous single channel systems. Three signal processing algorithms have been developed and tested using experimental data from a prototype. They have shown to be effective, as detailed in the thesis.
Keywords: signal processing; oil debris monitor; ODM; vibration sensor